Natural barriers facing female cyclists and how to overcome them: A cross national examination of bikesharing schemes - Richard Bean; Dorina Pojani; Jonathan Corcoran (Journal of Cycling and Micromobility Research)
Worldwide, the gender gap in urban cycling is considerable, with most cyclists being young to middle-aged men. In the current study, we first capture the suite of cycling barriers facing women before empirically investigating whether and how much three natural barriers (inclement weather, hilliness, and darkness) impact female users of bikesharing systems. For the analysis, we spatially integrate gender for more than 200 million bikesharing trips with fine-grained weather, gradient, and sunset/sunrise data. Computing a suite of the generalized additive models for ten cities worldwide covering a period of 14 years, we find that wind and precipitation disincentivise cycling, and more so for women than for men. Similarly, steeper gradients are a significant barrier for female bikeshare users for many cities. In every city, women make fewer trips in the dark (i.e., before sunrise and after sunset) compared to men. In higher-cycling cities, regardless of natural barriers, cycling declines less with age for women compared to other cities. To overcome the barriers presented by inclement weather, hilliness, and darkness we recommend (a) partial electrification of bikesharing fleets, (b) reduced exposure along bicycle paths (through manufactured shelters or tree canopies), and (c) adequate nighttime lighting along cycling paths. In the spirit of open science, all data and code on which this paper is based have been provided on Mendeley: https://data.mendeley.com/datasets/vmy42hywwx/1.